Proces pozyskiwania informacji o konkurencji - Pondel, Jolanta (The Process of Acquisition Competitive Information, 2007)
This paper shows the process of acquisition competitive information. It present why the process is so important today and how it should be done to get current sources for enterprises that want to take advantage of competitive enterprises on today's markets.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (11); 2007; nr 1156, s. 48-57